Caracterización físico - mecánica y química de las arcillas de la zona Sur-Este de la Cuenca Sedimentaria Miocénica de Loja - Díaz Capa, Wilman Hernán (2015)
The present investigation work has as objective the Characterization physique - mechanics and chemistry of the clays of the South area This of Cuenca Loja. Therefore they were carried out fieldworks to identify and to describe the places where the samples of clays were gathered that then were subjected to physical, chemical analysis and mechanics. The samples were gathered of the formations San Cayetano and Quillollaco, the analyses determined that the main composition is quartz with a bigger percentage to 60%, the surface values specify in 90% of the samples it is low, for such a reason it is attributed to the properties of the minerals of clay of the group of the kaolin. The tests of DRX made by Proinstra S.A. they allowed to corroborate the mineralogical composition being the quartz, caolinita, illita, Muscovite and group of the plagioclasas the most representative minerals, the montmorillonita that is a mineral of interest for its properties shows up in a significant way in W1P1. A map was elaborated to scale 1:15.000 indicating the places that present interest due to their mineralogical composition